Metaplastic breast carcinoma with osteogenic component - Maha SA Abdel Hadi; Maha Al-Madi; Thamer Wahba; Khalid Ghallab; Ali M Al-Amri (Saudi Journal of Medicine and Medical Sciences, 2014)
Metaplastic breast carcinomas (MBC) are rare primary breast malignancies characterized by the co-existence of carcinoma with non-epithelial cellular elements. They can be classified as monophasic spindle cell (sarcomatoid) carcinoma, biphasic carcinosarcoma, adenocarcinoma with divergent stromal differentiation (osseous, chondroid and rarely rhabdoid) as well as adenosquamous and pure squamous cell carcinomas. Nearly all reports portrait women in their forties or older, yet younger affected females in their twenties have been reported. The usual presentation included firm painless breast mass ranging between 1.4 and 14 cm in diameter, with no evidence of loco-regional or distal metastasis. Mammary osteosarcomas are aggressive tumors with a propensity for blood-borne rather than lymphatic spread. Metastatic disease expected to develop at a mean of 10.5 and 14.5 months from the initial diagnosis and demise followed within 20 months of the onset of metastasis. MBC remains a rare entity with poor response to both chemo-radiotherapy, histological diagnosis is challenging yet it is the main stay in outlining the management. The surgical option remains the only successful current treatment in the form of simple Mastectomy to achieve negative margins sparing the patients axillary node dissection.